Peranan Guru Dalam Menanamkan Rasa Percaya Diri Siswa di SMP PGRI 2 Bekri - Tesa Lonika Silvia; Irawan Suntoro; Hermi Yanzi (Jurnal Kultur Demokrasi, 2017)
The purpose of this study is to put explanation forward teachers role in giving students self-confidence at PGRI junior high school 2 Bekri Lampung Tengah Regency the year 2016/2017. Descriptive research was used with qualitative approach as the research method in this research. The research population was 67 respondents. The main data collecting technique used was questionnaire, and technique persetage was also used as the data analysis technique. Based on the data and result of the research. It had found the teacher has less role in giving students self-confidence, especially the teacher have not done yet their role meticulously as the educator in giving students sense of self-confidence. The teacher have not done yet their role meticulously as the trainer in giving students sense of self-confidence. And, The teacher have not done yet their role precisely as the motivator in giving students sense of self-confidence at the PGRI junior high school 2 Bekri the year 2016/2017.Penelitian ini bertujuan untuk menjelaskan peranan guru dalam menanamkan rasa percaya diri siswa di SMP PGRI 2 Bekri Kabupaten Lampung Tengah Tahun Pelajaran 2016/2017. Penelitian ini menggunakan metode penelitian deskriptif dengan pendekatan kuantitatif dengan populasi yang berjumlah 67 responden. Teknik pokok pengumpulan data menggunakan angket, analisis data menggunakan teknik presentase`Berdasarkan data dan hasil penelitian, diketahui guru kurang berperan dalam menanamkan rasa percaya diri siswa khususnya guru belum maksimal menjalankan peranannya sebagai pendidik dalam menanamkan rasa percaya diri, guru belum maksimal menjalankan peranannya sebagai pembimbing dalam menanamkan rasa percaya diri, guru belum maksimal menjalankan peranannya sebagai pelatih dalam menanamkan rasa percaya diri, dan guru belum maksimal menjalankan peranannya sebagai motivator dalam menanamkan rasa percaya diri siswa di SMP PGRI 2 Bekri tahun pelajaran 2016/2017.Kata kunci : peranan guru, rasa percaya diri, siswa